2014
DOI: 10.2139/ssrn.2509162
|View full text |Cite
|
Sign up to set email alerts
|

Combining Technology and Work Organization: An Analysis of Complementarity between IT and Decentralization across Firms of Different Size

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In our study, the technological frontier is defined as the distance to the median productivity level of companies. 23 Such an approach was also used by Rasel (2014) and Bloom et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the technological frontier is defined as the distance to the median productivity level of companies. 23 Such an approach was also used by Rasel (2014) and Bloom et al (2012).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, extant literature (e.g. Hitt and Brynjolfsson 1997;Heim and Peng 2010;Tambe, Hitt, and Brynjolfsson 2012;Rasel 2014) found that IT use on the job has a significant, positive impact on the level of autonomy. In this current study, thus we posit that:…”
Section: It-facilitated Autonomymentioning
confidence: 95%